A transcriptome analysis focusing on splenic immune-related mciroRNAs of rainbow trout upon Aeromonas salmonicida subsp. salmonicida infection. Issue 91 (August 2019) - Cao, Yongsheng; Wang, Di; Li, Shaowu; Zhao, Jingzhuang; Xu, Liming; Liu, Hongbai; Lu, Tongyan; Mou, Zhenbo
Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs that can regulate the immune responses during pathogen infection. Aeromonas salmonicida ( A. salmonicida ) subsp. salmonicida is the causative agent of furunculosis in salmon and trout. To identify the miRNAs and investigate the specific miRNAs in rainbow trout upon A. salmonicida subsp. salmonicida infection, we performed high throughput sequencing using the spleens of rainbow trout infected with and without an A. salmonicida subsp. salmonicida clinical isolate. A total of 381 known miRNAs and 926 novel miRNAs were identified. Eleven known and 16 novel miRNAs were found to be differentially expressed upon infection. The results of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses indicated that the target genes of the differentially expressed miRNAs were closely associated with immune responses and biological regulations. Additionally, over- and suppressed expression of miR-155–5p significantly enhanced and reduced the IL-2 and IL-1β expressions in RTG-2 cells induced by A. salmonicida, respectively. To our knowledge, this is the first experimental study on the miRNAs of rainbow trout upon A. salmonicida infection. The results here might lay a foundation for the further understanding of the roles of miRNAs in the immune responses during A. salmonicida infection in rainbow trout. Highlights: MiRNA responses to A. salmonicida infection were identified in rainbow trout by sequencing. 11 known and 16 novel miRNAs were differentially expressed during A. salmonicida infection. All the differentially expressed known miRNAs were predicted to be involved in immunity. MiR-155–5p was proved to promote the inflammation induced by A. salmonicida.